2006
DOI: 10.1002/bip.20552
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between bovine serum albumin and gemini surfactant alkanediyl‐α, ω‐bis(dimethyldodecyl‐ammonium bromide)

Abstract: Interactions between bovine serum albumin (BSA) and cationic gemini surfactant alkanediyl-alpha,omega-bis(dimethyldodecyl-ammonium bromide) (12-n-12, n=3, 4, 6) in aqueous solution have been investigated by measuring fluorescence, UV-vis transmittance, dynamic lighting scattering, and circular dichroism. Compared to a traditional surfactant dodecyltrimethylammonium bromide (DTAB), 12-n-12 interacts with BSA more strongly. With increasing concentration, 12-n-12 first binds specifically onto BSA leading to the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 33 publications
(30 reference statements)
0
43
0
1
Order By: Relevance
“…The theoretical and experimental studies on the adsorption behaviour of proteinsurfactant mixtures have been covered by a number of papers [72][73][74][75][76], and different mechanisms for the displacement of protein molecules from the interface by the surfactants have been suggested such as orogenic displacement [75] or competitive adsorption [76]. In many investigations [77][78][79][80][81], interaction of cationic gemini surfactants with proteins have exposed that such surfactants interact more competently with proteins as compared to conventional single-chain surfactants because of their distinctive aggregation properties such as lower critical micelle concentration (CMC) and Krafft temperature, special aggregation morphology, strong hydrophobic microdomains and so forth [82][83][84][85]. Cationic surfactants, being antimicrobial, have attracted attention with respect to their interaction with deoxyribonucleic acid (DNA) and lipids [86].…”
Section: Nonionic Surfactantsmentioning
confidence: 99%
“…The theoretical and experimental studies on the adsorption behaviour of proteinsurfactant mixtures have been covered by a number of papers [72][73][74][75][76], and different mechanisms for the displacement of protein molecules from the interface by the surfactants have been suggested such as orogenic displacement [75] or competitive adsorption [76]. In many investigations [77][78][79][80][81], interaction of cationic gemini surfactants with proteins have exposed that such surfactants interact more competently with proteins as compared to conventional single-chain surfactants because of their distinctive aggregation properties such as lower critical micelle concentration (CMC) and Krafft temperature, special aggregation morphology, strong hydrophobic microdomains and so forth [82][83][84][85]. Cationic surfactants, being antimicrobial, have attracted attention with respect to their interaction with deoxyribonucleic acid (DNA) and lipids [86].…”
Section: Nonionic Surfactantsmentioning
confidence: 99%
“…Following the procedure of Pi et al [39], the average number of LYCl molecules bound to a BSA molecule, , was calculated for the different surfactant concentrations. Fig.…”
Section: Binding Of Lycl To Bovine Serum Albumin Bsamentioning
confidence: 99%
“…In a recent study [12] we had reported the interaction of a cationic gemini and its monomeric counterpart CTAB at low surfactant concentrations (which is a common practice for studying protein-surfactant interactions) wherein the conformational changes and saturation points in the proteins (BSA, HSA, RSA) were found to occur at much lower [gemini] in comparison to [CTAB]. Some other investigations [13][14][15][16][17][18] on the interaction of cationic gemini surfactants with proteins have revealed that these surfactants interact more efficiently with proteins as compared to conventional single chain surfactants because of their unique aggregation properties [19]. In order to further explore and acquire detailed knowledge of the phenomenon, it is, therefore, of interest to study the protein-surfactant interaction at higher cationic surfactant concentrations.…”
Section: Introductionmentioning
confidence: 97%